2011
DOI: 10.1016/j.neuroimage.2011.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-specific electrocorticographic correlates of working memory delay period fMRI activity

Abstract: Electrocorticography (ECoG) and functional MRI (BOLD-fMRI) have been used previously to measure brain activity during working memory delay periods. These studies have separately reported oscillation changes in the theta (4-8 Hz) band and BOLD-fMRI increases during delay periods when information is maintained in memory. However, it is not known how intracranial cortical field potential (CFP) changes relate to BOLD-fMRI responses during delay periods. To answer this question, fMRI was obtained from six epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 55 publications
7
34
0
Order By: Relevance
“…Moreover, even in the absence of these imaging problems, the spatial precision of the iEEG remains dependent on how precisely the localization of the electrodes is performed with respect to the real (rather than modeled) brain anatomy and on how much tissue deformation (brain shift) is induced by the electrode implantation (Lachaux et al, 2003). Brain shift varies strongly from patient to patient, depending on the location and size of craniotomy, the number and placement of electrodes, and the presence and severity of any post-surgical swelling and the distortions of the tissue relative to the cortical surface reconstructions can reach the order of one centimeter (Khursheed et al, 2011). Therefore, our approach for electrode projection, which is identical to that presented by Hermes and colleagues (Hermes et al, 2010) for the special case of electrode strips, could be not as accurate as in previous works based on more advanced and precise methods (see, e. g., Dalal et al, 2008;Dykstra et al, 2012;Hermes et al, 2010;Swann et al, 2009;Tertel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, even in the absence of these imaging problems, the spatial precision of the iEEG remains dependent on how precisely the localization of the electrodes is performed with respect to the real (rather than modeled) brain anatomy and on how much tissue deformation (brain shift) is induced by the electrode implantation (Lachaux et al, 2003). Brain shift varies strongly from patient to patient, depending on the location and size of craniotomy, the number and placement of electrodes, and the presence and severity of any post-surgical swelling and the distortions of the tissue relative to the cortical surface reconstructions can reach the order of one centimeter (Khursheed et al, 2011). Therefore, our approach for electrode projection, which is identical to that presented by Hermes and colleagues (Hermes et al, 2010) for the special case of electrode strips, could be not as accurate as in previous works based on more advanced and precise methods (see, e. g., Dalal et al, 2008;Dykstra et al, 2012;Hermes et al, 2010;Swann et al, 2009;Tertel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To empirically verify this choice, we considered two representative case subjects for which more than one electrode was located within 15 mm of an area of significant fMRI activity (Khursheed et al, 2011) and evaluated the overlap between this area and the area of significant gamma iEEG activity resulting from the cortical spread, at multiple values of d max (0.5, 1.0, 1.5 and 2.0 cm) for iEEG and multiple p-values for fMRI (p = 0.001, 0.01, 0.05). The overlap was calculated as the (percent) ratio between the vertex counts of the intersection and the vertex counts of the union, of the two patches of significant gamma iEEG (p = 0.05) and significant fMRI activity (p = 0.05, 0.01 and 0.001).…”
Section: Cortex-based Inter-subject Ieeg-fmri Distributed Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, ECoG studies demonstrate that low- and high-frequency activity often share an inverse relationship [5,20,24,25,38,39,40]. Likewise, while measures of high-frequency amplitude show overlap with the BOLD measures of fMRI, low-frequency activity is anatomically dissociated with BOLD measures [41]. …”
Section: High-frequency Responses and Memorymentioning
confidence: 99%
“…Hermes et al (2011), in their study on LFP-BOLD coupling in motor function, suggested that BOLD signal change was largely induced by high gamma power increase and alpha-beta power decrease in the primary motor area. Furthermore, Khursheed et al (2011) stressed that theta power decrease had the most negative correlation with BOLD responses in working memory on the frontal lobe. On the basis of previous studies and our own, HGA-BOLD coupling is a promising key to identify complex human brain functions.…”
Section: Figmentioning
confidence: 99%